ANALISIS HASIL BELAJAR SISWA KELAS V BERDASARKAN MULTIPLE INTELLIGENCES DI SDN 1 MIJEN - Ira Rizwana; F. Shoufika Hilyana; Fatikhatun Najikhah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to identify the types of multiple intelligences possessed by fifth-grade students at SD 1 Mijen. Multiple intelligences refer to the various kinds of intelligence that each individual uses to solve different life problems and produce works that guide their lives by utilizing their unique intelligence and competencies. Essentially, every child born into this world is neither dumb nor unintelligent, but possesses different types of intelligence.This research employs a qualitative method with a descriptive approach to be conducted at SD 1 Mijen, Kaliwungu District, Kudus Regency. The focus of the study is multiple intelligences, with data collection techniques including observation, interviews, documentation, and recording. The data analysis used is descriptive qualitative analysis.The results of the study indicate that fifth-grade students at SD 1 Mijen have diverse multiple intelligences, including linguistic, visual-spatial, intrapersonal, logical-mathematical, and interpersonal intelligences.